Influence Competence and Quality Service Against Performance Employees at PDAM Makassar City - Ibrahim Ibrahim; Syarifuddin Syarifuddin; Haeruddin Haeruddin; Iqbal AR (Syntax Idea)
The purpose of this study is to test and analyze the significant effect of competence on employee performance in PDAM Makassar City, test and analyze the significant effect of service quality on employee performance in PDAM Makassar City, and test and analyze competence and service quality simultaneously. a significant effect on employee performance in PDAM Makassar City. This research was conducted at the Makassar City PDAM Office, with a population of 477 people and a sample of 265 people ( Slovin formula). The data analysis used is descriptive to explain the research data, while to analyze quantitative data using Multiple Linear Regression analysis. The results found that competence showed a positive and significant influence on employee performance. The competencies shown by employees based on knowledge, skills, experience and mastery attitudes determine the achievement of PDAM Makassar City employees' performance. Service quality has a positive and significant effect on employee performance. The quality of service applied by employees is in accordance with the variety of expertise, task identity, task significance, service autonomy and feedback, thereby contributing to the improvement of PDAM Makassar City employee performance. Simultaneously, competence and service quality have a positive and significant effect on employee performance. Improving employee performance in quantity, quality, efficiency, effectiveness and loyalty cannot be separated from the competence of employees and the quality of services applied to PDAM Makassar City customers.